Rediscovering the sense of pleasure in morality - Festin, Lorenz Moises J. (Animo Repository, 2022)
Pleasure has always been an important issue in morality. And although ethical systems tend to focus the discussion on human action, this agreeable sentiment has remained a recurrent question in moral philosophy. In this paper, I go back to Aristotle’s treatment of pleasure in his writings, particularly in the Nicomachean ethics. I will argue that the distinction he draws between bodily pleasures and those of the mind, represents an important point not only in understanding eudemonia but also in situating the very nature of ethical debates today. I will try to show how Aristotle’s distinction among pleasure matches up with his differentiation between Energeia and kinesis as well as with the distinction between praxis and poiesis, and how these differentiations have enabled Aristotle to evade the pitfall of hedonism.